(untitled) (Revista Internacional de Formação de Professores, 2016)
The reflection on the praxis influences the awareness of the complexity of the teaching act which presupposes questioning, analysis and processing, and leads to more and better learning and therefore professional development. Using reflection before, during and after the action (the different phases/stages of the supervision cycle), the training of the teachers-to-be’s training future teacher has to be more careful and committed to the training process, as it enables the improvement and development of skills through identifying and becoming aware of the weaknesses of oneself and the other and experiencing ways of thinking and being a teacher. Our study is based on a qualitative methodology and the field of research focuses specifically on training practices of students / future teachers. This study aims at analyzing the very discourse of the participants in order to understand how to perceive their development as people and as professionals, making use of the categories of Target Language Observation Scheme (TALOS). TALOS enables content analysis of their reflections on three classes observed which reveals a self-portrait of professional practice. As a tentative conclusion, we found an improvement of process capabilities of observation and self-observation of the study subjects.